Studies on combining ability of half diallel derived rice hybrids generated using landraces x advanced breeding lines of North East India - M, James; P, Magudeeswari; Lap, Bharati; Maibam, Urmila; Behera, Abhilash; Dake , Deepika; K, Lokeshkumar; Tyagi, Wricha; Rai, Mayank (ORYZA-An International Journal of Rice, 2024)
North East (NE) India, the centre of origin of rice is blessed with landraces like Kala Joha, Chakhao Poireiton (CP) and Mynri, Jwain from Assam, Manipur, and Meghalaya respectively. NE India is a hotspot for rice blast disease and it can cause a loss in grain yield from 30-100%. Rice breeding in NE India should focus on developing rice varieties/ hybrids utilizing the local landraces and their diverse gene pool. Hence, six landraces and four advanced breeding lines were crossed in half diallel fashion and the F1s were evaluated for ten agro-morphological and two rice blast disease related traits. Half-diallel analysis using Griffing’s numerical method was adopted to obtain combining ability effects. Significantly high general combining ability (GCA) effects for grain yield per plant (GYPP) were observed in Mynri (2.7**) and CAUS107 (2*), whereas it was negative for CP (-2.2**). Crosses between landraces and advanced breeding lines gave high GYPP like, CAUS103 x Kasalath (24.3±4g) and CAUS107 x Kala Joha (21.4±1.5g), they also showed higher SCA effects of 10.3 and 6.4 respectively. Lowest disease affected spikelets per panicle (DSPP) was observed in Mynri x CAUS126 (0.2±0.03) and lowest leaf blast (LB) scores (1) were recorded in Jwain x CAUS107, Blm x CAUS107 and Blm x CAUS103.